Overexpression of integrin α11 induces cardiac fibrosis in mice. (30th August 2017) - Romaine, A.; Sørensen, I. W.; Zeltz, C.; Lu, N.; Erusappan, P. M.; Melleby, A. O.; Zhang, L.; Bendiksen, B.; Robinson, E. L.; Aronsen, J. M.; Herum, K. M.; Danielsen, H. E.; et al.
Abstract: Aim: To understand the role of the collagen‐binding integrin α 11 in vivo, we have used a classical approach of creating a mouse strain overexpressing integrin α 11. A transgenic mouse strain overexpressing α 11 in muscle tissues was analysed in the current study with special reference to the heart tissue. Methods: We generated and phenotyped integrin α 11 transgenic (TG) mice by echocardiography, magnetic resonance imaging and histology. Wild‐type (WT) mice were subjected to aortic banding (AB) and the expression of integrin α 11 was measured in flow cytometry‐sorted cardiomyocytes and non‐myocytes. Results: TG mice developed left ventricular concentric hypertrophy by 6 months, with increased collagen deposition and reactivation of mRNA encoding foetal genes associated with cardiovascular pathological remodelling compared to WT mice. Masson's trichrome staining revealed interstitial fibrosis, confirmed additionally by magnetic resonance imaging and was found to be most prominent in the cardiac septum of TG but not WT mice. TG hearts expressed increased levels of transforming growth factor‐ β 2 and transforming growth factor‐ β 3 and upregulated smooth muscle actin. Macrophage infiltration coincided with increased NF‐ κ B signalling in TG but not WT hearts. Integrin α 11 expression was increased in both cardiomyocytes and non‐myocyte cells from WT AB hearts compared to sham‐operated animals. Conclusion: We report for the first time that overexpression of integrin α 11 induces cardiac fibrosis and left ventricular hypertrophy. This is a result of changes in intracellular hypertrophic signalling and secretion of soluble factors that increase collagen production in the heart.